1976
DOI: 10.1111/j.1365-246x.1976.tb01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Velocity dispersion due to anelasticity; implications for seismology and mantle composition

Abstract: The concept of a relaxation spectrum is used to compute the absorption and dispersion of a linear anelastic solid. The Boltzmann aftereffect equation is solved for a solid having a linear relationship between stress and strain and their first time derivatives, the 'standard linear solid', and having a distribution of relaxation times. The distribution function is chosen to give a nearly constant Q over the seismic frequency range. Both discrete and continuous relaxation spectra are considered. The resulting li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
370
1
6

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 758 publications
(381 citation statements)
references
References 28 publications
4
370
1
6
Order By: Relevance
“…In this paper we apply the absorption band concept [Liu et al, 1976;Kanamori and Anderson, 1977;Anderson et al, 1977;Anderson and Minster, 1980;Minster and Anderson, 1981] to the attenuation of body waves, surface waves, and free oscillations. The basic method is described by Anderson and Hart [1978a, b] except that we replace the frequencyindependent Q assumption with the absorption band assumption.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we apply the absorption band concept [Liu et al, 1976;Kanamori and Anderson, 1977;Anderson et al, 1977;Anderson and Minster, 1980;Minster and Anderson, 1981] to the attenuation of body waves, surface waves, and free oscillations. The basic method is described by Anderson and Hart [1978a, b] except that we replace the frequencyindependent Q assumption with the absorption band assumption.…”
Section: Introductionmentioning
confidence: 99%
“…1: zero for negative time and decaying to a constant positive value for positive times (Christensen 1982). This can be approximated with a discrete relaxation spectrum (Liu et al 1976)…”
Section: Preliminariesmentioning
confidence: 99%
“…A first method to transform the stress-strain relation into a differential form using Padé approximations is introduced by Day & Minster (1984). Later, Emmerich & Korn (1987) and Carcione et al (1988) suggested to improve this by approximating the medium properties with a discrete relaxation spectrum (Liu et al 1976) and fitting the parameters used to describe this spectrum to the observed behaviour numerically. These methods are still common today (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The constant-Q model is closely related to the notion of a continuous absorption band, i.e. a continuous distribution of relaxation mechanisms that lead to nearly frequency-independent absorption (Liu et al, 1976), as shown in Figure 11.6. This is in contrast to the appearance of isolated absorption peaks that are, for instance, commonly found in metals (e.g.…”
Section: Description Of Seismic Wave Attenuation Basic Observables Amentioning
confidence: 99%
“…the frequency-dependence of phase velocity (Figure 11.6). In the constant-Q model (Liu et al, 1976), the phase velocity dispersion relation is given by 19) where ω ref is a reference frequency. Equation (11.19) holds, provided that Q >> 1, and that ω lies within the absorption band.…”
Section: Description Of Seismic Wave Attenuation Basic Observables Amentioning
confidence: 99%